Tilings, Patterns and Technology - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2011)
In this paper we discuss various situations where tilings and patterns, with the aid of technology, facilitate the teaching of mathematics and serve as tools in understanding and developing new mathematical ideas. We also illustrate how technology makes possible cultural connections in the study of mathematics using Islamic tilings and patterns.